2011
DOI: 10.1091/mbc.e10-08-0722
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 requires Arf6-mediated membrane dynamics to efficiently enter and infect T lymphocytes

Abstract: As Arf6 is key to coordinating plasma membrane trafficking and regulates cellular invasion by several microorganisms, the authors studied Arf6 function during early HIV-1 infection. The data suggest that HIV-1 requires Arf6-driven plasma membrane dynamics and depends on GTP/GDP activity to efficiently fuse, enter, and infect CD4+ T lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 91 publications
3
74
0
1
Order By: Relevance
“…5D and E). The magnitude of this effect was similar to that previously reported to occur with ARF silencing (16). Under these conditions, ARF-6 knockdown did not inhibit HLA-A2 downmodulation in HIV-infected (Gag ϩ ) cells (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…5D and E). The magnitude of this effect was similar to that previously reported to occur with ARF silencing (16). Under these conditions, ARF-6 knockdown did not inhibit HLA-A2 downmodulation in HIV-infected (Gag ϩ ) cells (Fig.…”
Section: Resultssupporting
confidence: 89%
“…ARF-6 is known to regulate cellular entry by several microorganisms, including HIV, and ARF-6 silencing has been shown to inhibit HIV infection (16). Therefore, we used inhibition of HIV infection as a positive control for ARF-6 silencing.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that ARF6 depletion does not affect cell infection by HIV-1 vectors pseudotyped with the VSV-G protein 33 . To determine whether ESCRT machinery involved in viral budding was functionally affected or not by ARF6 depletion, we infected MCF-7 cells, depleted or not for ARF6, with VSVpseudotyped replication competent HIV-1.…”
Section: Arf6 Regulates Exosomesmentioning
confidence: 98%
“…Since actin remodeling should help the released HIV core to penetrate the cortical actin layer [26,36] (Fig. 3), the requirement for signaling and actin dynamics has been interpreted as evidence for HIV fusion with the PM [13,34,37]. The regulation of actin dynamics through CXCR4 signaling is particularly important for HIV infection of resting CD4 + T cells [37,38].…”
Section: Fusion With the Plasma Membranementioning
confidence: 99%